Hybrid Bilayer PLA/Chitosan Nanofibrous Scaffolds Doped with ZnO, Fe3O4, and Au Nanoparticles with Bioactive Properties for Skin Tissue Engineering - Radwan-Pragłowska, Julia; Janus, Łukasz; Piątkowski, Marek; Bogdał, Dariusz; Matýsek, Dalibor (Polymers, 2020)
Burns affect almost half a million of Americans annually. In the case of full-thickness skin injuries, treatment requires a transplant. The development of bioactive materials that promote damaged tissue regeneration constitutes a great alternative to autografts. For this reason, special attention is focused on three-dimensional scaffolds that are non-toxic to skin cells and can mimic the extracellular matrix, which is mainly composed of nanofibrous proteins. Electrospinning, which enables the preparation of nanofibers, is a powerful tool in the field of biomaterials. In this work, novel hybrid poly (lactic acid)/chitosan biomaterials functionalized with three types of nanoparticles (NPs) were successfully developed. ZnO, Fe3O4, and Au NPs were investigated over their morphology by TEM method. The top layer was obtained from PLA nanofibers, while the bottom layer was prepared from acylated chitosan. The layers were studied over their morphology by the SEM method and their chemical structure by FT-IR. To verify their potential in burn wound treatment, the scaffolds' susceptibility to biodegradation as well as moisture permeability were calculated. Also, biomaterials conductivity was determined in terms of electrostimulation. Finally, cytotoxicity tests were carried out by XTT assay and morphology analysis using both fibroblasts cell line and primary cells. The hybrid nanofibrous scaffolds displayed a great potential in tissue engineering.
Keywords: biomedical applications; electrospinning; hybrid polymer scaffolds